Pendampingan Kesehatan, Kemandirian Dan Aktifitas Fungsional Sehari Hari Pada Lansia Di Panti Werdha Tresno Mukti - Sri Sunaringsih Ika Wardojo; Rakhmad Rosadi; Azhar Ihza Pamedar Sabda; Safun Rahmanto (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
Community service was carried out at the Tresno Mukti Nursing Home with several activities including providing Activities of Daily Living (ADL) Questionnaires, providing Physical Activity Therapy Education. The total population at the Tresno Mukti Werdha Nursing Home is 23 elderly people, with the condition of the body being able to walk independently without needing assistance tools or other people a total of 11 elderly people, with disabilities with a total of 9 elderly people, bedressed with 3 elderly people who know the elderly. Outreach Results Research describing the level of independence of the elderly (69-90 years) in fulfilling daily living activities shows that a small proportion of the elderly at the Light Dependence Level are 4 elderly people (36.3%) to the normal level of 7 elderly people (63.6%). running smoothly, and as knowledge material for the elderly and caregivers, especially the condition of decreasing independence and daily functional activities by providing education Physical Activity Therapy aims to provide opportunities for behavior change for various physical, psychological and environmental problems for the elderly)